COMPARISON ANALYSIS OF WORK CONFLICT WITH WORK STRESS ON PERFORMANCE OF EMPLOYEE SMALL MEDIUM INDUSTRIAL AND TRADING COOPERATIVE DEPARTMENT IN MEDAN CITY - Mindo Donnauli Simangunsong; Akhmad Taufik; Surya Asih (Jurnal Scientia, 2023)
This study aims to examine and analyze the comparison of work conflict with work stress on the performance of employees of the Medan City Trade and Industry SME Cooperative Office. The population of this study were employees of the Medan City Trade and Industry SME Cooperative Office. The research method used is the census method, where the entire population is used as the research sample. The data collection technique is a questionnaire. Hypothesis testing using multiple regression analysis with the Statistical Package for Social Science (SPSS) program. The results showed that the variables of work conflict and work stress affect employee performance partially, simultaneously, and determine R². From the independent variable that has the greatest significant value on employee performance is work stress compared to work conflict